Analysis of the fundamental characteristics of diamond-like crystals and low-dimensional structures - Litovchenko, V.G. (Condensed Matter Physics, 2004)
The principle has been developed for systematizing the diamond-like crystals with tetrahedral structure of the elementary cells and with valence chemical bonds, based on the calculation of the lattice constant. The approach proposed permits to predict basic parameters such as energy gap Eg , electron affinity (optical work function) X, mechanical hardness H, melting temperature Tm , optical phonon frequency etc. These parameters have been calculated and the table is presented for a number of chemical compositions. For materials with mixed chemical bonds (valence and ionic) the corrections can be calculated using Pouling electronegativity conception. The comparison with experiment demonstrates good agreement between the latter and the proposed procedure. Запропонований принцип системного опису параметрів алмазоподібних кристалів з тетраедричною структурою елементарної комірки та з валентним типом хімічного зв’язку, що базується на розрахунку постійної гратки. Запропонований підхід дозволяє передбачити такі фундаментальні параметри речовин, як ширину забороненої зони Eg , електронну спорідненість (оптичну роботу виходу) X, механічну твердість H , температуру плавлення Tm , граничну частоту оптичних фононів та ін. Пропонується таблиця названих параметрів для численних речовин, в тому числі нових. Для матеріалів зі змішаним іонно-ковалентним типом хімічного зв’язку розраховані поправки, використовуючи принцип електронегативності Полінга. Порівняння з експериментом демонструє добре узгодження.